Implementasi Konsep Pariwisata Halal Pada Sektor Perhotelan dan Restoran Serta Strategi Pengembangan di Indonesia - Shafa Unnida; Hermida Adityas; Lisnawati Lisnawati (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Halal tourism is one of the fastest-growing sectors, driven by the increasing needs of Muslim travelers for services that comply with Islamic principles. Indonesia, as a country with a Muslim-majority population, has significant potential to develop this sector, particularly in the hotel and restaurant industries, which play an important role in supporting tourism activities. This study aims to analyze the implementation of halal tourism concepts in the hotel and restaurant sectors and to identify the challenges and development strategies in Indonesia. The method used is a literature review by examining various sources such as scientific journals, books, and relevant reports published within the last five years. The results show that the implementation of halal tourism has been carried out through the provision of prayer facilities, assurance of halal food and beverages, and services that support the comfort of Muslim travelers. However, its implementation still faces several challenges, including limited human resources, uneven halal certification, lack of public awareness, and suboptimal regulatory and infrastructure support. In addition, promotion and branding of halal tourism still need to be strengthened to reach a wider market. Therefore, integrated development strategies are needed, including improving human resource quality, strengthening regulations, accelerating halal certification, and optimizing promotion and collaboration among stakeholders. The findings of this study are expected to serve as a reference for the government and business actors in developing halal tourism that is more competitive, inclusive, and sustainable in Indonesia.